Flavonoids from Clerodendrum genus and their biological activities - Mamuaja, Meiske Naomi; Herlina, Tati; Rumampuk, Rymond Jusuf; Maksum, Iman Permana; Rukayadi, Yaya (International Association of Physical Chemists, 2024)
Background and purpose: Many studies have been performed to identify new sources, their optimal isolation, and the biological activities of flavonoids due to nutraceutical, pharmaceutical, and cosmeceutical properties. Experimental approach: This review describes the method for flavonoid isolation and characteristic from the Clerodendrum genus and their biological activities with the indication of the most active ones. To perform a comprehensive review, a thorough literature review using Google Scholar, Scopus, and Science Direct was performed with keyword alone or in combination with other words. Key results: The isolation and identification of flavonoids from the Clerodendrum genus have revealed a variety of compounds using various methods. Various studies conducted in vivo, in vitro and in silico also reported bioactivities of these flavonoids. Conclusion: Several factors determine the flavonoid content in the Clerodendrum genus, among others, the different parts of the plant, extraction techniques, and solvent combination used. Isolated flavonoids also show significant biological activities, such as antioxidant, antiinflammatory, antimicrobials, antidiabetic, anticancer, anti-tyrosinase, and neuroprotective agents.